The challenges and opportunities of commercialisation - Howard, Sophie (New Zealand Science Review, 2011)
​Government is challenging New Zealand public research organisations to increase the rate of commercialisation of intellectual property (IP) and research findings. It is generally accepted that a high-tech economy offers the potential to increase GDP through exports of high-value products, and this view is well supported within universities. However, in practice, academic staff face conflicting incentives and pressures to invest their time and succeed in the university environment. Commercialisation managers work at the interface of the university culture and the external business world, and manage the conflicting philosophies and drivers of each side. Unlike ‘translators,’ these individuals add value by creating opportunities and proactively managing the supply and demand of early-stage, high-risk ideas. Viclink, the commercialisation arm of Victoria University of Wellington, has been in turnaround mode for the past 24 months in an aim to deliver increased value from its research and IP, and has seen first-hand the challenges of working in the market for innovation. New Zealand universities have approached and scoped their roles quite differently. Around the world different models and priorities exist for commercialisation and tech transfer of university IP. A recent case study on a clean tech start-up company highlights several of the observations and opportunities in commercialising publicly funded research, and on the relationships between inventors, commercialisation companies, incubators and investors. This discussion provides a summary of current challenges and opportunities in commercialisation, as observed by practitioners in a university setting.